Screening of active solid catalysts for esterification of tall oil fatty acids with methanol. (1st July 2017) - Kocík, Jaroslav; Samikannu, Ajaikumar; Bourajoini, Hasna; Pham, Tung Ngoc; Mikkola, Jyri-Pekka; Hájek, Martin; Čapek, Libor
Abstract: The paper is focused on the description of the activity/selectivity of mesoporous silica based materials loaded with various types of active species in the esterification of tall oil free fatty acids. The metals such as aluminium, molybdenum, gallium and zinc, including their combinations were impregnated on the mesoporous silica, which was tested in esterification reaction. All these catalysts preserved its tall oil free fatty conversion in the first and the second catalytic cycles. However, while only insignificant amount of gallium or molybdenum was lost from the solid catalyst into the liquid phases, zinc leached from every studied solid catalyst. In contrast to impregnated gallium on mesoporous silica, which exhibited higher acidity and higher tall oil free fatty acids conversion in the first catalytic cycle, but its value was not preserved in the second catalytic test.